URGENSI PENERAPAN KONSEP OMNIBUS LAW DALAM RANCANGAN UNDANG-UNDANG IBU KOTA NEGARA - Hotmauli, Yemima Andria; Kusuma, Nadya Enjelin; Marchelya, Vanya (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The plan to relocate the capital city is necessary to address geographic, economic, and social disparities, particularly as 57.4% of Indonesia's population is concentrated on Java, making it more densely populated compared to other islands. The current development, which is heavily centralized on Java, also hampers the equitable distribution of investment and impacts the overall economy. The relocation of the capital requires the implementation of an omnibus law, which consolidates various regulations into a single comprehensive law. The omnibus law aims to simplify and streamline overlapping regulations, especially those related to the capital relocation. This approach is considered effective in simplifying existing regulations, with recommendations for careful restructuring and additions to ensure its proper implementation.